Effectiveness of metoprolol in preventing atrial fibrillation and flutter in the postoperative period of coronary artery bypass graft surgery - Ribeiro, Jorge Pinto (2004)
Objective - To assess the effectiveness of metoprolol in preventing clinically detectable atrial fibrillation (AF) and flutter after coronary artery bypass graft (CABG) surgery . Methods - An open, randomized study was carried out to treat 200 patients who had undergone isolated CABG surgery with extracorporeal circulation. The patients were randomized to either receive metoprolol orally or not to receive the medication in the postoperative period. The outcomes were the detection of sustained atrial AF and flutter, which were symptomatic or required treatment. The patients with the following characteristics were excluded from the study: baseline left ventricular ejection fraction < 35%; previous AF; history of bronchospasm; second- and third-degree atrioventricular blocks, low cardiac output, and heart failure. Results - Arrhythmias occurred in 11 out of 100 patients in the metoprolol group and in 24 out of 100 patients in the control group (P=0.02). The relative risk (RR) was 0.46 (95% CI = 0.24-0.88), and the number necessary to treat (NNT) and avoid the outcome was 8 patients. AF was the arrhythmia most frequently observed (30/35). In 38 patients aged 70 years or more, the arrhythmias occurred in 2 out of 19 patients in the metoprolol group and in 10 out of 19 patients in the control group (χ2 Yates: P=0.01). The relative risk was 0.20 (95% CI = 0.05-0.79) and the number necessary to treat was 2 patients. Conclusion - Metoprolol is effective in preventing AF and flutter in the postoperative period of CABG surgery, and this effect was more evident in the group of elderly patients.